A cognitive study of lexical expressions denoting motion in english and vietnamese - Th.S Lý Ngọc Toàn (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This dissertation aims to illustrate lexical expressions denoting motion in English and Vietnamese from cognitive linguistic perspectives including their semantic and syntactic properties. In terms of the semantic properties, the dissertation delves into the mapping of the semantic components to linguistic surface forms while the syntactic properties are explored in the opinion of the logical incorporation of surface forms with the conceptual basis of grammar. More particularly, the lexical expressions of motion are investigated in a consistent conglomeration of motion verbs with spatial prepositions, which used to be analyzed in isolation in several previous studies. In doing so, the dissertation sheds light on the linguistic properties of lexicalization patterns, uncovers human conceptual structures of motion, and provides in-depth insights into the distinct models of motion. Hopefully, this dissertation makes a considerable contribution to language study, be it language teaching and translation. To achieve the set aims, the key theories of cognitive linguistics which are adopted to underpin this dissertation consist of lexicalization patterns and construction grammar. The former is concerned with the semantic properties, which is an examination of the conflation of semantic components to the surface forms, and the latter involves the syntactic properties, which is an investigation into the logical incorporation of surface forms with the conceptual basis of grammar including argument structures and event structures. Moreover, multiple methods are employed to collect as well as analyze data, which are qualitative and quantitative, deductive and inductive, and descriptive and comparative. The data were collected by building the corpora in English and Vietnamese from the two sources including twelve English and Vietnamese short stories and three novels. The findings of the research illustrate how English and Vietnamese speakers express different patterns of motion in words and show the differences between lexical expressions in English and Vietnamese. iv We conclude that the differences between lexical expressions in English and Vietnamese are not only related to the linguistic properties but the properties of conceptualization as well.